Using Human Rights to Hold the US Accountable for its Anti-Sex Trafficking Agenda: The Universal Periodic Review and new directions for US policy - Lerum, Kari; McCurtis, Kiesha; Saunders, Penelope; Wahab, Stéphanie (Anti-Trafficking Review, 2012)
Since the passing of the Trafficking Victims Protection Act of 2000, anti-trafficking efforts have grown in funding, political strength, and popular-culture appeal in the United States and globally. Particularly influential in shaping anti-trafficking policy in the United States are anti-prostitution advocates who are primarily concerned with rehabilitating sex workers and eradicating sexual commerce. Simultaneous to the development of prohibitionist anti-trafficking and anti-prostitution efforts in the US, movements for sex worker rights have also grown in strength and visibility, influencing a variety of cultural, academic, and public health arenas. While sex worker activists have widened the dialogue around sex workers’ rights, their